A needs-based approach to curriculum development for the training of literacy teachers. - Kola, Soraya (My University, 1995)
The purpose of this study was to develop a curriculum for the training of literacy teachers using a needs-based approach. Over 15 million adults are illiterate in South Africa and this could seriously hamper the new nations's reconstruction and development if not tackled effectively. To date the focus in the field has .been the development of a national examination and curricula for learners. However little is being done to prepare the teachers who will have to take learners through the new system. It has therefore been the focus of this research project to establish the needs of these teachers and providers and thereafter to develop a training course that would address their needs.(Abbreviation abstract)
A research report submitted in part fulfilment of the requirements of the Master of Education degree (Coursework and Research Report) of the University of the Witwatersrand.
Keywords: Functional literacy -- Study and teaching -- South Africa.; Teachers -- Training of -- South Africa.